ingkat motivasi siswa dalam pembelajaran pendidikan jasmani olahraga dan kesehatan materi bola voli di SMAN 1 tanjung tahun 2023 - Mohamad Rivaldi; Rusdiana Yusuf; Adi Suriatno (Jurnal Pengetahuan dan Pendidikan, 2024)
This research seeks to determine the extent of students' motivation in playing volleyball at SMAN 1 Tanjung. So the goal to be achieved is the school's reference for re-examining obstacles in the process of teaching and learning activities in physical education subjects. The research method used was a survey method among students at SMAN 1 Tanjung. This type of research is descriptive. The instrument used in this research at SMAN 1 Tanjung was in the form of a questionnaire containing student statements. The results of this research can be concluded that as many as 41 students have motivation in playing volleyball which is in the Very High category with a percentage range (81.25% - 100%), and as many as 9 students have motivation in playing volleyball which has the category High with a percentage range (62.49% - 81.24%). So it can be concluded that student motivation in playing volleyball is very high.